2009
DOI: 10.1016/j.devcel.2009.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Bone Ridge Patterning during Musculoskeletal Assembly Is Mediated through SCX Regulation of Bmp4 at the Tendon-Skeleton Junction

Abstract: SUMMARY During the assembly of the musculoskeletal system, bone ridges provide a stable anchoring point and stress dissipation for the attachment of muscles via tendons to the skeleton. In this study, we investigate the development of the deltoid tuberosity as a model for bone ridge formation. We show that the deltoid tuberosity develops through endochondral ossification in a two-phase process: Initiation is regulated by a signal from the tendons, whereas the subsequent growth phase is muscle-dependent. We the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

22
335
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 273 publications
(362 citation statements)
references
References 62 publications
22
335
1
Order By: Relevance
“…Constitutively activated Smad1 overexpression was reported to induce myoblast osteogenic differentiation, whereas nuclear translocation of Smad4 inhibited myoblast myogenic differentiation [34]. It is not known whether Smad proteins and MSX2 also function to inhibit osteogenic differentiation and promote TDSC tenogenic differentiation, as reported in previous studies [30,32,34]; further study is required. Other factors, such as mechanical loading [35] and local extracellular matrix environment [9], may also function to suppress TDSC osteogenesis inside the tendon midsubstance.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…Constitutively activated Smad1 overexpression was reported to induce myoblast osteogenic differentiation, whereas nuclear translocation of Smad4 inhibited myoblast myogenic differentiation [34]. It is not known whether Smad proteins and MSX2 also function to inhibit osteogenic differentiation and promote TDSC tenogenic differentiation, as reported in previous studies [30,32,34]; further study is required. Other factors, such as mechanical loading [35] and local extracellular matrix environment [9], may also function to suppress TDSC osteogenesis inside the tendon midsubstance.…”
Section: Discussionmentioning
confidence: 77%
“…However, the myogenic differentiation potential of TDSCs has not been formally investigated and requires further study. Despite this, the potential of TDSCs to establish and maintain the TBJ and musculotendinous junction is plausible based on a previous study [30]. It has been reported that bone ridge formation was initiated by tendons, whereas the subsequent growth phase was muscle dependent [30].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations